صبرکے قرآنی مفاہیم :سورۃ الفاتحہ کے تناظر میں سورۃ البقرہ کا توقیفی مطالعہ : Quranic Concepts of Patience: A Critical Study of Surah Al-Baqarah in the Context of Surah Al-Fatiha - Mian Inaam ur Rehman (DIRAYAT, 2024)
The interrelationship of various subjects mentioned in the Holy Qur'an plays a vital role in interpreting Islamic teachings. Surah Al-Fatiha is important in understanding and interpreting the Holy Quran. The subjects indicated in Surah Al-Fatiha show that it summarizes the entire Qur'anic message. From this point of view, it can be said that the Quran as a whole contains the details of the facts mentioned in Surah Al-Fatiha. In this regard, it is necessary to understand the various surahs of the Holy Qur'an in the light of Surah Al-Fatiha regarding various topics. This analytical approach also makes the connection between different surahs clear. This article guides us toward understanding the themes of Surah Al-Baqarah regarding the concept of patience in the context of Surah Al-Fatiha.